Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Which point lies on the line described by the equation below?

[tex]\[ y + 3 = 2(x - 1) \][/tex]

A. [tex]\((2, 9)\)[/tex]
B. [tex]\((2, 1)\)[/tex]
C. [tex]\((1, -4)\)[/tex]
D. [tex]\((0, 0)\)[/tex]
E. [tex]\((1, -3)\)[/tex]
F. [tex]\((-1, -6)\)[/tex]


Sagot :

To determine which point lies on the line described by the equation [tex]\( y + 3 = 2(x - 1) \)[/tex], we start by converting the given equation into the slope-intercept form, [tex]\( y = mx + b \)[/tex], where [tex]\( m \)[/tex] is the slope and [tex]\( b \)[/tex] is the y-intercept.

First, let's rearrange the given equation:

[tex]\[ y + 3 = 2(x - 1) \][/tex]

Distribute the 2 on the right side:

[tex]\[ y + 3 = 2x - 2 \][/tex]

Subtract 3 from both sides to isolate [tex]\( y \)[/tex]:

[tex]\[ y = 2x - 2 - 3 \][/tex]

Simplify the equation:

[tex]\[ y = 2x - 5 \][/tex]

Now we have the line in slope-intercept form: [tex]\( y = 2x - 5 \)[/tex].

Next, we need to check which points satisfy this equation. We will substitute the coordinates of each point into the equation [tex]\( y = 2x - 5 \)[/tex] and see which one holds true.

A. [tex]\((2, 9)\)[/tex]:

Substitute [tex]\( x = 2 \)[/tex] and [tex]\( y = 9 \)[/tex]:

[tex]\[ 9 = 2(2) - 5 \][/tex]
[tex]\[ 9 = 4 - 5 \][/tex]
[tex]\[ 9 = -1 \][/tex]

This is not true.

B. [tex]\((2, 1)\)[/tex]:

Substitute [tex]\( x = 2 \)[/tex] and [tex]\( y = 1 \)[/tex]:

[tex]\[ 1 = 2(2) - 5 \][/tex]
[tex]\[ 1 = 4 - 5 \][/tex]
[tex]\[ 1 = -1 \][/tex]

This is not true.

C. [tex]\((1, -4)\)[/tex]:

Substitute [tex]\( x = 1 \)[/tex] and [tex]\( y = -4 \)[/tex]:

[tex]\[ -4 = 2(1) - 5 \][/tex]
[tex]\[ -4 = 2 - 5 \][/tex]
[tex]\[ -4 = -3 \][/tex]

This is not true.

D. [tex]\((0, 0)\)[/tex]:

Substitute [tex]\( x = 0 \)[/tex] and [tex]\( y = 0 \)[/tex]:

[tex]\[ 0 = 2(0) - 5 \][/tex]
[tex]\[ 0 = 0 - 5 \][/tex]
[tex]\[ 0 = -5 \][/tex]

This is not true.

E. [tex]\((1, -3)\)[/tex]:

Substitute [tex]\( x = 1 \)[/tex] and [tex]\( y = -3 \)[/tex]:

[tex]\[ -3 = 2(1) - 5 \][/tex]
[tex]\[ -3 = 2 - 5 \][/tex]
[tex]\[ -3 = -3 \][/tex]

This is true.

F. [tex]\((-1, -6)\)[/tex]:

Substitute [tex]\( x = -1 \)[/tex] and [tex]\( y = -6 \)[/tex]:

[tex]\[ -6 = 2(-1) - 5 \][/tex]
[tex]\[ -6 = -2 - 5 \][/tex]
[tex]\[ -6 = -7 \][/tex]

This is not true.

Therefore, the point that lies on the line [tex]\( y + 3 = 2(x - 1) \)[/tex] is:

E. [tex]\((1, -3)\)[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.